TODAY’S COUPLE, TOMORROW’S FAMILY—A STUDY OF THE RESILIENCE SHOWN BY CERTAIN MALE HOMOSEXUAL COUPLES IN HAVANA - Novales Armenteros, José Manuel (Revista Sexología y Sociedad, 2016)
IN CONTEXTS WHERE INDIVIDUALS WITH A SEXUAL ORIENTATION DIFFERENT FROM HETERONORMATIVITY ARE OVERTLY OR COVERTLY REJECTED, ISOLATED, THEIR RIGHTS VIOLATED AND THEIR PERSONALITIES LACERATED, SAME-SEX COUPLES FIND IT VERY DIFFICULT TO DEVELOP A FUNCTIONAL AND FULL RELATIONSHIP. GIVEN THESE CIRCUMSTANCES, A BOND BASED ON LOVE, GENUINE ATTRACTION AND COMMITMENT IS NOT AN OPTION FOR THESE COUPLES BUT RATHER A MUST. THIS, HOWEVER, IS NOT ENOUGH. THEY HAVE TO DEAL WITH THE CRUEL HOMOPHOBIA SO DEEPLY ROOTED IN THE SUBJECTIVE COLLECTIVE MEMORY AND MANIFESTED IN SOCIALIZING SPACES. FORTUNATELY, THERE ARE RESILIENT COUPLES WHO HAVE OVERCOME THESE DIFFICULTIES AND, OCCASIONALLY, THIS RELATION HAS CONSOLIDATED. THESE COUPLES ARE THE FOCUS OF THIS STUDY, AIMED AT CHARACTERIZING THE STRENGTHS THAT DEFINE THEM AS RESILIENT. A QUALITATIVE METHODOLOGY WAS USED TO STUDY SIX SAME-SEX COUPLES IN HAVANA FROM A SYSTEMIC, POSITIVE, AND PERSONAL-DEVELOPMENT ORIENTED PERSPECTIVE. RESEARCH FINDINGS SHOWED THAT THE GREATEST ADVERSITIES FACED BY THESE COUPLES STEM FROM HOMOPHOBIA, IN THE WAKE OF WHICH SEVERAL SOCIOPSYCHOLOGICAL CONFIGURATIONS EMERGE TURNING THE COUPLE RELATIONSHIP INTO A SAFE SPACE FULL OF SATISFACTION AND POTENTIALITIES FOR ITS MEMBERS. KNOWING THE DYNAMIC OF RESILIENT COUPLES WILL UNDOUBTEDLY ENABLE US TO TAKE MORE ADEQUATE PREVENTION, PROMOTION AND INTERVENTION ACTIONS IN PURSUIT OF EQUALITY AND HAPPINESS OF INDIVIDUALS, COUPLES, AND FAMILIES. KEY WORDS: SAME-SEX COUPLES, RESILIENCE, RISK FACTORS, PROTECTIVE FACTORS